Optimized indoor radio signal prediction with 3D ray tracing model at 2.4 and 5 GHz - Tarapiah, Saed; Sulaiman, Batoul; Natsheh, Emad; Atalla, Shadi; Abu Kharmeh, Suleiman; Rashed, Abdallah (Bulletin of Electrical Engineering and Informatics, 2025)
Channel propagation models are essential in developing efficient wireless communication networks. Indoor propagation relies on the nature of the surrounding environment. Therefore, many researchers have provided different ways for effective propagation modeling and received power prediction. In this paper, ray-tracing-based site-specific propagation models are presented. The actual measurements are obtained using many wireless access points (AP) based on IEEE 802.11 with different technologies a/b/g and n as transmitters and mobile phone with a proposed mobile application used as a receiver to collect the power at different locations called reference points (RPs), these measurements are done without the existence of people movement. The simulation results are obtained using wireless InSite simulator depends on 3D shoot and bounce ray (SBR) method. The simulation measurements are assessed by comparing it with the actual measurements and they analyze statistically such that the correlation coefficient R between them reaches up to 80% which is an indicator to an acceptable agreement. Path loss characteristic affected by the building materials and distance along the receiver’s route is evaluated.